TINJAUAN ATAS PROSEDUR PENGUJIAN SUBSTANTIFTERHADAP PENJUALAN DAN PIUTANG USAHA PADA PT X OLEH KAP KUMALAHADI, KUNCARA, SUGENG PAMUDJI DAN REKAN JAKARTA (KAP KKSP & REKAN JAKARTA) - Devita Sandra, (2021)
The purpose of writing this final report is to find out the implementation of substantive testing procedures on sales and accounts receivable at PT X which was audited by KAP KKSP and Jakarta Partners. Substantive testing is a procedure that has been designed by the auditor to detect errors that will affect the correctness of account balances. PT X is a company engaged in manufacturing and trading that produces machine tools and then sells the tools it has produced. PT X is making sales on credit, where this sale results in accounts receivable transactions. Therefore, both accounts will be subjected to substantive testing to check whether there is a recording error. The procedure for substantive testing of PT X's sales and receivables is carried out by starting an audit plan, namely understanding the business entity, direct examination, determining materiality limits and preparing an audit program. In the sales and accounts receivable audit there are several things that need to be done, namely checking client records, analytical testing, recalculation and determining samples to trace evidence. In accounts receivable audit, sampling is used to create and send accounts receivable confirmation letters to clients. So that the implementation of the substantive testing procedures can be concluded that the sales and receivables of PT X can be presented fairly and do not cause material misstatements.